The labor market consequences of impatience - Brian C. Cadena (IZA World of Labor, 2016)
Standard economic theory suggests that individuals know best how to make themselves happy. Thus, policies designed to encourage “better” behaviors will only reduce people's happiness. Recently, however, economists have explored the role of impatience, especially difficulties with delaying gratification, in several important economic choices. There is strong evidence that some people have trouble following through on investments that best serve their long-term interests. These findings open the door to policies encouraging or requiring better behaviors, which would allow people to commit to the choices they truly want to make.
Keywords: D91; I26; J24; J31; J62; J64; 330; impatience; dynamic inconsistency; educational investment; job search; lifetime earnings